Limited immune response conferred by an E2-CSFV expressing DNA vaccine after booster vaccination in murine models - Allaudin, Zeenathul Nazariah; Mohd Lila, Mohd Azmi; Abdul Rahman, Sheikh Omar; Bahaman, Abdul Rani; Ideris, Aini; Mutalib, Abdul Rahim (Veterinary Association Malaysia, 2009)
To investigate if intradermal (ID) and intramuscular (1M) routes of vaccination result in a comparable expression of E2 gene of classical swine fever virus (CSFV), an established E2 DNA construct was tested in murine experimental models. Groups of six mice received three pcDNA+E2 immunisation each at weeks 0, 4 and 8 by either ID via gene gun delivery or 1M. Another second batch of six mice was immunised in a similar protocol with a plasmid cocktail of pcDNA+E2 and immunomodulators (pBOOST-rnIL4/mIL13). The findings showed that the 1M route was better in immune induction compared to the gene gun method. Apparently, on the basis of E2 expression in skin tissues via ID, ear targeting seemed to be better than the abdominal skin approach. With respect to the kinetics of anti-E2 antibody production, the antibody was not formed after one and two months after the DNA immunisation, but reached its detection level at 10 weeks post-immunisation. Variations were observed in the ability of the E2 expression plasmids to induce immune response in murine model when the humoral and cell-mediated immunity (CMI) was determined by ELISA and DTH trials, respectively. The adopted ID and 1M immunisation approaches gave distinct immune induction patterns in the presence and absence of cytokines. The findings indicate the enhancement of immune response after co-administration of these genetic immunomodulators with DNA vaccine against CSFV. However, the difference was insignificant (P>0.05) due to the high variance caused by the presence of non-responsive individuals.